From the Discovery of Targets to Delivery Systems: How to Decipher and Improve the Metallodrugs' Actions at a Molecular Level - Ilaria Iacobucci; Sara La Manna; Irene Cipollone; Vittoria Monaco; Luisa Canè; Flora Cozzolino (MDPI AG, 2023)
Metals are indispensable for the life of all organisms, and their dysregulation leads to various disorders due to the disruption of their homeostasis. Nowadays, various transition metals are used in pharmaceutical products as diagnostic and therapeutic agents because their electronic structure allows them to adjust the properties of molecules differently from organic molecules. Therefore, interest in the study of metal-drug complexes from different aspects has been aroused, and numerous approaches have been developed to characterize, activate, deliver, and clarify molecular mechanisms. The integration of these different approaches, ranging from chemoproteomics to nanoparticle systems and various activation strategies, enables the understanding of the cellular responses to metal drugs, which may form the basis for the development of new drugs and/or the modification of currently used drugs. The purpose of this review is to briefly summarize the recent advances in this field by describing the technological platforms and their potential applications for identifying protein targets for discovering the mechanisms of action of metallodrugs and improving their efficiency during delivery.